Komparace motivačních programů vybraných podniků - Teturová, Vendula; Myšková, Renáta (Univerzita Pardubice, 2010)
This article deals with the comparison of specific employee motivation programs in areas of remuneration, social policy and employee education. After the definition of theoretical background there is a brief description of survey methodology. The data were gathered from the web sites of selected companies. Then this article includes the characterization of these enterprises as well as the comparison of specific employee motivation programs. The conclusion involves the improvement suggestions of these programs.
Keywords: motivation; motivation program; personnel policies; remuneration; education and training; human resources management